2016
DOI: 10.1016/j.micres.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of 3″-demethyl-gentamicin C components by gen N disruption strain of Micromonospora echinospora and test their antimicrobial activities in vitro

Abstract: Gentamicin consists primarily of four components, which have different patterns of methylation at C-6' position. The methyl groups have a significant impact on gentamicin antimicrobial activity. Sequence analysis predicted that GenN was a methyltransferase in the gentamicin biosynthetic pathway. To study the function of genN, it was disrupted in Micromonospora echinospora. The genN disruption strains produced 3″-N-demethyl-gentamicin C complex instead of the gentamicin C complex. In this study, 3″-N-demethyl g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…For 6 of these, the structure could be determined by MS and MS n methods, and structures could also be proposed for 13 others ( 27 ). In previous work it has been shown that levels of certain metabolites with altered methylation patterns are enhanced upon deletion of either genN ( 19 , 28 ) or genK ( 20 ). We therefore set out systematically to alter the complement of known methyltransferase genes and to study the metabolites produced.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For 6 of these, the structure could be determined by MS and MS n methods, and structures could also be proposed for 13 others ( 27 ). In previous work it has been shown that levels of certain metabolites with altered methylation patterns are enhanced upon deletion of either genN ( 19 , 28 ) or genK ( 20 ). We therefore set out systematically to alter the complement of known methyltransferase genes and to study the metabolites produced.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 19 candidate genes (GenBank accession nos. MF036118–MF036131 and MF036134–MF036138) were identified using the BLASTP program ( 28 ), with percentage sequence identities to GenN ranging from 26.67 to 40.35% ( SI Appendix , Table S4 ). Each candidate gene was cloned into expression vector pET28a(+) in Escherichia coli , and cell extracts were assayed for their ability to catalyze SAM-dependent conversion of C2 into C1, monitored by LC-ESI-HRMS ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the biosynthetic gene cluster of gentamicin was identified more than a decade ago, we and others have elucidated most of the gentamicin biosynthetic pathway in Micromonospora echinospora ATCC15835 [8][9][10][11][12][13][14][15][16][17][18][19] and revealed crystal structures of several of the enzymes involved in the biosynthesis 14,20,21,22 . GenD2, GenN, GenS2 and GenD1 have been demonstrated to be involved in the formation of gentamicin X2 16,21,22 .…”
mentioning
confidence: 99%